(untitled) (Journal of Informatics and Mathematical Sciences, 2011)
The object of the present paper is to introduce the sequence spaces λ_0 (F, p) defined by the sequence of fuzzy numbers and p=(p_k) be any bounded sequence of positive real numbers. We study their different algebraic and topological properties. We also obtain some inclusion relations between these spaces.